Preparation of (Tb0.94−xLu0.06Hox)2O3 transparent ceramics with high Verdet constants for magneto-optical applications - Yaozhi Wang; Wei Jing; Weiwei Li; Tao Xu; Jie Li; Renxin Zhang; Xilong Qin; Jian Chen; Binchu Mei (Journal of Advanced Ceramics)
Magneto-optical transparent ceramics exhibiting the Faraday effect provide new opportunities for optical isolator applications. In this study, magneto-optical transparent ceramics (Tb0.94−xLu0.06Hox)2O3 (x = 0, 0.005, 0.01, 0.0125, and 0.015) were successfully fabricated by reducing atmosphere sintering and hot isostatic pressing (HIP) posttreatment. The effects of x on the microstructure, in-line transmittance, and magneto-optical properties were studied. The addition of Ho3+ promoted the densification of the ceramics, increasing their transmittance, with the in-line transmittance of (Tb0.93Lu0.06Ho0.01)2O3 reaching 79.05% at 1064 nm. Importantly, the Verdet constant was influenced by the doping of Ho3+. The highest Verdet constant of (Tb0.925Lu0.06Ho0.015)2O3 was approximately −404 rad·T−1·m−1, which was approximately 6% greater than that of the undoped sample and more than 3 times that of the terbium gallium garnet (TGG) crystal.